PENGARUH FAKTOR FUNDAMENTAL DAN FAKTOR MAKROEKONOMI TERHADAP HARGA SAHAM (Survei Sektor Telekomunikasi Pada Indeks LQ45 Periode 2019-2022) - Iwan Sugianto,; Fitriani, Fitriani; Lilis Hasta Hastiana , (Journal of Innovation Research and Knowledge, 2024)
The study aimed to determine the effect of fundamnetal factor and macroeconomicfaktor on telecommunications sector stock prices. This study uses financial management theory related to the variables of stock prices, Earning Per Share, Debt To Equity Ratio, Inflasi, Economic Growth. The Research method used in descriptive quantitative. The sample in this study is a telecommunications sector that is registered on LQ45 used is 4 companies with a period of 2019-2022 The data analysis used is multiple regression analysis using Eviews 9 Software. The results of this study are based on the t test on EXCL, TLKM, TOWR Earning Per Share, Debt To Equity Ratio, Inflation, Economic Growth Rate does not significantly affect stock prices. At the TBIG company, the Debt To Equity Ratio has a significant effect on stock prices. Based on the F test, it shows Earning Per Share, Debt To Equity Ratio, Inflation, and Economic Growth simultaneously or jointly have a significant effect on the stock prices of TLKM and TBIG companies